Autonomous teams as a way to increase the engagement of nonprofit members (case study) - Stankiewicz Janina; Łychmus Patrycja; Bortnowska Hanna (Management, 2019)
In the literature on management, engagement is generally discussed in the context of cooperation with paid employees. This article focuses on the rarely analyzed issue – developing the engagement of nonprofit members. Research was carried out on this subject in the association in Zielona Góra, where deficits were found in that area. The aim of the article is to determine the reasons for the low engagement among SPOzZD members, to identify their expectations towards the functioning of the Association as well as to indicate activities that could encourage further engagement of these members, which can be implemented by representatives of the Board. The case study method was used.